2018
DOI: 10.1016/j.tre.2018.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Volatility forecasting across tanker freight rates: The role of oil price shocks

Abstract: This paper examines whether the inclusion of oil price shocks of different origin as exogenous variables in a wide set of GARCH-X models improves the accuracy of their volatility forecasts for spot and 1-year time-charter tanker freight rates. Kilian's (2009) oil price shocks of different origin enter GARCH-X models which, among other stylized facts of the tanker freight rates examined, take into account the presence of asymmetric and long-memory effects. The results reveal that the inclusion of aggregate oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Shi, Yang, and Li, (2013), by employing the framework of Kilian (2009), have shown that demand shocks of oil do not affect the tanker freight rates but on the contrary it is the supply shocks that have an effect on them. Despite this findings, Gavriilidis, Kambouroudis, Tsakou, and Tsouknidis (2018) have shown that the inclusion of aggregate oil demand shocks and oil-specific demand shocks improves the explanatory power of the forecasted volatility of 1 year time charter rates for all the vessel sizes.…”
Section: Literature Reviewmentioning
confidence: 80%
“…Shi, Yang, and Li, (2013), by employing the framework of Kilian (2009), have shown that demand shocks of oil do not affect the tanker freight rates but on the contrary it is the supply shocks that have an effect on them. Despite this findings, Gavriilidis, Kambouroudis, Tsakou, and Tsouknidis (2018) have shown that the inclusion of aggregate oil demand shocks and oil-specific demand shocks improves the explanatory power of the forecasted volatility of 1 year time charter rates for all the vessel sizes.…”
Section: Literature Reviewmentioning
confidence: 80%
“…They found that oil market volatility has a significant influence on the tanker market. Gavriilidis et al [14] discovered that considering oil demand shocks significantly improves the forecasting accuracy of tanker freight rate volatility, while considering oil supply shocks has a very limited influence on the volatility forecasting results. Maitra et al [15] investigated the volatility transmission between oil and liner shipping stock returns using dynamic conditional equicorrelations and the directional spillover index approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The definition and pricing of freight is an important activity for logistics systems. There are many variables to consider in this pricing and, according to Gavriilidis et al [35] and Sánchez-Díaz [36], sustainability aspects must be considered in this analysis.…”
Section: Logistics Systemsmentioning
confidence: 99%